A contextual evaluation of alcoholic beverages using the repertory grid method - SCRIVEN, F. M.; GAINS, N.; GREEN, S. R.; THOMSON, D. M. H. (International journal of food science & technology, 1989)
Summary Twenty subjects were used to investigate the contexts in which they typically consumed a range of alcoholic beverages. Contexts were elicited using the repertory grid method, and five principal components were found to describe the perceptual dimensions common to most people. The poles of these dimensions are summarily interpreted as: thirstquenching vs. not; formal meal vs. social drinking environment; before meals vs. after meals; in a pub vs. outside a pub; consumed neat vs. mixed. The ways in which this information can be used to develop marketing strategies and influence product development are discussed.